Neuroprotective and neuroregenerative properties of haruan (channa striatus) traditional formulation - Mohd Shafri, Mohd Affendi (2012)
Neurodegenerative conditions continue to affect a large number of people. Despite numerous studies carried out in the last few decades, no effective treatment has been found and current management of neurodegenerative conditions are not effective,marred by side-effects, costly and could only provide symptomatic alleviations. Haruan or Channa striatus, is rich in many important amino acids and fatty acids, which may act as suitable pharmacological modulators to neuron cells as they have potential to cross the blood-brain barrier efficiently and have anti-oxidative action and may trigger neurite growth receptor on neuron cell’s surface. The neuroprotective and neuroregenerative effects of haruan traditional formulation (HTF) on PC12 cell line, an established cell line used for studying neurite outgrowth, was first studied to see its effect of cell growth behaviour, morphology and neurite outgrowth. From the study, HTF appears to influence neurite outgrowth, cell morphology and growth behaviour in PC12 cells in concentration dependent manner. It was found that HTF at 100 μL in the serum rich assay was most effective in providing protection against cell death as well as in stimulating greatest neurite extension (p < 0.001, one way ANOVA with Tukey’s post hoc test). Next, in in vivo experiment using Sprague Dawley rats, the effect of HTF on rats’ nose-dipping and rearing behaviours in neuroprotective and neuroregenerative assays, in which two neurodegenerative agents, ketamine and methamphetamine given intraperitoneally, 4 four times a day at 2 hour interval at different doses were used, was studied using a hole board maze. It was found that HTF could provide some neuroprotective (p < 0.01 for the nose dip and p < 0.05 for rearing; one way ANOVA with Tukey’s post hoc analysis) and neuroregenerative (p < 0.001 for both nose dip and rearing; one way ANOVA with Tukey’s post hoc analysis) effects on rats behaviour for the LEK group only. Consequent change in hippocampus was assessed by further analyses of the hippocampus CA3 region in terms of live neuron cell count, and pathological change in the overall structural integrity by staining the hippocampal sections using cresyl violet stains. Cell counting was done using Java-Installed Image J software, images were captured using a Nikon Ti Inverted Fluorescent Microscope and Imaging software and data was statistically analysed using a Sigma Plot 11.0 for Windows. It was found that the best effect in term of preservation of structural integrity and regeneration of live cell number (p < 0.001 one way ANOVA with Tukey’s post hoc analysis) was in the LEK. The HTF is less able to produce positive changes in the methamphetamine-treated groups which may be used to identify the mode of actions of HTF’s neurorestorative mechanism in future research. In view of other results however correlation between functional, numerical and structural changes is not straightforward. Although there is evidence of neuroprotective and neuroregenerative effects, HTF must be studied further for more conclusive evidence.